Effect of Additives on Rheological Properties of Invert Emulsions - A.R Mohammed, Muhanned; Ali Abed Mohammed, Samar (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This research deals with study of the effect of additives on rheological properties (yield point, plastic viscosity ,and apparent viscosity) of emulsions. Twenty seven emulsion samples were prepared; all emulsions in this investigation are invert emulsions when water droplets are dispersed in diesel oil. The resulting emulsions are called water-in-oil (W/O) emulsions. The rheological properties of these emulsions were investigated using a couett coaxial cylinder rotational viscometer (Fann-VG model 35 A), by measuring shear stress versus shear rate. It was found that the effect of additives on rheological properties of emulsions as follow: the increase in the concentration of asphaltic material tends to increase the rheological properties of emulsions, the increase in the volume percentage of barite tends to increase the rheological properties of emulsions and the increase in the volume percentage of emulsifier has a little effect on the value of rheological properties, but in the same time it increase the stability of emulsions with temperature because it surrounded water droplets.